2011
DOI: 10.1111/j.1447-0756.2010.01421.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep deprivation, physical activity and low income are risk factors for inadequate weight gain during pregnancy: A cohort study

Abstract: Risk factors for inadequate gestational weight gain were low income, being multiparous, sleep deprivation, physical activity in terms of standing and walking, and the male sex of baby.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 33 publications
2
53
1
Order By: Relevance
“…Women who slept for ten hours or more were nearly twice as likely to exceed 2009 IOM recommendations compared to women who reported less than eight hours of sleep nightly. While these results are contrary to findings from Althuizen et al, which links a reduction in nocturnal sleep with increased GWG [19], a larger study has recently identified sleep deprivation as a risk factor for inadequate GWG [46]. When we compared sleep duration in the “low” versus “normal” GWG groups we found no significant difference.…”
Section: Discussioncontrasting
confidence: 99%
“…Women who slept for ten hours or more were nearly twice as likely to exceed 2009 IOM recommendations compared to women who reported less than eight hours of sleep nightly. While these results are contrary to findings from Althuizen et al, which links a reduction in nocturnal sleep with increased GWG [19], a larger study has recently identified sleep deprivation as a risk factor for inadequate GWG [46]. When we compared sleep duration in the “low” versus “normal” GWG groups we found no significant difference.…”
Section: Discussioncontrasting
confidence: 99%
“…33,66,67 Insomnia is associated with significant morbidities including an increased risk for depression, 18 stress, 65,68 and inadequate or excessive gestational weight gain. 69,70 Although depression and stress are well known consequences of insomnia, fewer studies have evaluated insomnia in relation to gestational weight gain. Women are expected to gain adequate weight to support the growing fetus.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] It has been reported that pre-gestational BMI is strongly associated with metabolic changes in the levels of biochem-ical markers 7,8 and patterns of weight gain, which constitute alterations that occur in women's bodies to facilitate fetal development. [1][2][3][4][5][6] It has been reported that pre-gestational BMI is strongly associated with metabolic changes in the levels of biochem-ical markers 7,8 and patterns of weight gain, which constitute alterations that occur in women's bodies to facilitate fetal development.…”
Section: Introductionmentioning
confidence: 99%